Fine control of Curie temperature of magnetocaloric alloys La(Fe, Co, Si)13 using electrolytic hydriding. (15th January 2020) - Guo, Liya; Lovell, Edmund; Tang, Qiwei; Boldrin, David C.; Tang, Chiu C.; Day, Sarah J.; Cohen, Lesley F.; Ryan, Mary P.
Abstract: This work demonstrates precision control of hydrogen content in La(Fe, Co, Si)13 Hδ for the development of environmentally friendly magnetocaloric-based cooling technologies, using an electrolytic hydriding technique. We show the Curie temperature, a critical parameter which directly governs the temperature window of effective cooling, can be varied easily and reproducibly in 1 K steps within the range 274 K to 402 K. Importantly, both partially (up to 10%) and fully hydrided compositions retain favorable entropy change values comparable to that of the base composition. Crucially, we show in these second-order phase transition compounds, partial hydriding is stable and not susceptible against phase separation. Graphical abstract: Unlabelled Image